PENGARUH PENGEMBANGAN PEGAWAI TERHADAP KUALITAS PELAYANAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SAMBAS - Arif Waskito Wibowo E.42008006 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
AbstractThis Skripsi is aim to analyse the factors influencing service quality in Dinas Kependudukan danPencatatan Sipil of Sambas Regency, specially at factor of officer training. This title Skripsi is liftedto know whether officer training really influencing of service quality, so that can become the inputto government to more improving the service quality specially at Dinas Kependudukan danPencatatan Sipil of Sambas Regency. The research location is in Dinas Kependudukan danPencatatan Sipil of Sambas Regency. Sampel Research is 20 operator of kependudukan area andconducting training at regency level in 2010. Conclusion in this research is officer training have anbig effect on service quality in Dinas Kependudukan dan Pencatatan Sipil of Sambas Regency.Level of influence of officer training to service quality is equal to 84,0% and the rest of it is 16,0%influenced by other dissimilar factor which not checked in this research like leadership factor, motivate the officer, reward (appreciation) and facility supporting in fluency of service process.Keyword : Officer Training, Service Quality